Chemical composition and antioxidant properties of the essential oil of Cinnamomum altissimum Kosterm. (Lauraceae) - Abdelwahab, S.I.; Mariod, A.A.; Taha, M.M.E.; Zaman, F.Q.; Abdelmageed, A.H.A.; Khamis, S.; Sivasothy, Y.; Awang, Khalijah (Elsevier, 2017)
The essential oil of the bark of Cinnamomum altissimum Kosterm. obtained by hydrodistillation was analyzed by capillary GC and GC–MS. The oil was characterized by linalool (36.0%), methyl eugenol (12.8%), limonene (8.3%), α-terpineol (7.8%) and terpinen-4-ol (6.4%). The content of total phenolics in the extracts was determined spectrometrically according to the Folin–Ciocalteu procedure and calculated as gallic acid equivalents (GAE). A total phenolic compound was 50.41 ± 0.98 μg GAE/mg oil. The extract displayed antioxidant activities, with an IC50 value of 38.5 ± 4.72 μg/ml, using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, and 345.2 ± 14.8 μM Fe (II)/g dry mass using ferric reducing/antioxidant power (FRAP) assay.